Prlekija-Međimurje dialect language contact - Tjaša Jakop (Hrvatski Dijalektološki Zbornik, 2017)
This paper presents linguistic data from the eastern part of the Slovenian-Croatian border. The paper will examine the phonology, morphology and lexica of dialects in this bordering linguistic territory, and draw a comparison of linguistic features of Pannonian dialects on Slovenian side (Gibina, Ljutomer, Cven) and Kajkavian dialect on Croatian side (Banfi). An interesting example is grammatical category of dual number (a specific morphological category preserved in various Slovenian dialects) which is also preserved to the present day in some areas in neighbouring countries, i.e. in Kajkavian Croatia (Banfi). Dialects on both sides of the border show a lot of similarity in many linguistic aspects. These common features are reflexes for short and long stressed schwa (< *, *- and *-): ˈmẹːša, sˈnẹːxa, ˈdeːšč, ˈpeːs, ˈmeːgla; reflexes for long ě (< *) and ǫ (< *̄): bˈrẹːskva, čˈrẹːšja, mˈlẹːkọ, sˈnẹːk; ˈrọːka, ˈsọːset, ọbˈrọːč, gọˈlọːp etc. The decline of the dialect in (bordering) Croatian villages and the erosion of communicative competence across the generations (especially following separation from Yugoslavia and the new political border between Slovenia and Croatia), combined with the fact that the standard language in village Banfi is Croatian, calls for more intensive and wider research which would include more villages in this particular area.